Illegal Polygamy in the Era of the New Penal Code: Protection of Wives' Rights and the Enforcement Direction of Articles 402–403 of Law Number 1 of 2023 on the Criminal Code - Riyani, Devi (Green Publisher Indonesia, 2026)
Background: The practice of illegal polygamy, conducted without court permission or the wife's knowledge, remains a persistent issue in Indonesia, undermining the legal protection of women's rights in marriage. The enactment of Law Number 1 of 2023 concerning the National Criminal Code (KUHP) introduces new provisions that criminalize such actions, potentially shifting the paradigm from viewing polygamy violations as mere administrative or civil offenses. Objective: This research aims to analyze the legal protection afforded to wives involved in illegal polygamy under the current marriage law regime and to assess the relevance and direction of enforcing Articles 402 and 403 of the 2023 KUHP in strengthening this protection. Methods: This study employed a normative juridical approach with a legislative and conceptual focus. It examines primary legal materials, including the Marriage Law, the Compilation of Islamic Law (KHI), and the 2023 KUHP, alongside secondary legal materials such as scholarly articles and legal expert opinions. Data were analyzed qualitatively through interpretation of legal norms and assessment of normative synchronization. Findings: The research reveals that while the Marriage Law and KHI provide preventive and repressive civil mechanisms for wife protection, these instruments have structural limitations, particularly when polygamy is conducted secretly. Articles 402-403 of the 2023 KUHP introduce an additional layer of protection by criminalizing marriage conducted despite a lawful obstacle or concealment of marital status. However, the effectiveness of these criminal provisions depends on a synchronized interpretation with marriage law, particularly regarding the concept of